Preventing Child Behavior Problems in the Erlangen-Nuremberg Development and Prevention Study: Results from Preschool to Secondary School Age - Lösel, Friedrich; Stemmler, Mark (International Journal of Conflict and Violence (IJCV), 2012)
A brief overview of the prevention part of the long-term Erlangen-Nuremberg Development and Prevention Study, which combines a prospective longitudinal and experimental design. Findings up to five years after intervention are reported. From a sample of 609 families with kindergarten children, subgroups participated in the universal prevention program EFFEKT (child social skills training, a parent training and a combination of both) or were assigned to equivalent control groups. The short-term evaluation showed significant effects in mediating constructs (social problem solving and parenting behavior) and in educators’ ratings of children’s social behavior. In a follow-up after two to three years, school report cards showed fewer children with multiple behavior problems. In a further follow up after four to five years program children reported fewer externalizing and internalizing problems than the control group. There were no significant effects in the mothers’ reports on their children’s behavior. Most significant effect sizes ranged between d = 0.20 and d = 0.40. The findings suggest various positive long-term effects of the intervention. However, one need to be cautious with regard to over-generalizing the positive findings, because effect sizes vary over time and the positive findings could not be replicated in all investigated variables.